Why Researchers Should Publish Archive Inventories Online: The Case of the Archives of French Equatorial Africa - (:unkn) unknown (My University, 2016)
Abstract: This short report gives the rationale behind the creation of the website https://archivescolonialesbrazzaville.wordpress.com/ , dedicated to the colonial archives of French Equatorial Africa in January 2015. It is argued that researchers and archivists can build highly useful websites in Africa even with a limited Internet connection.
Keywords: African Research